Exploring Satisfaction and Migration Intentions of Physicians in Three University Hospitals in Poland - Dubas-Jakóbczyk, Katarzyna; Domagała, Alicja; Kiedik, Dorota; Peña-Sánchez, Juan Nicolás (International journal of environmental research and public health, 2019)
Introduction: University hospitals constitute a unique group of health care organizations which traditionally link three functions: (1) providing highly specialized services, (2) teaching activities, and (3) conducting research. Objectives: To assess the level of carrier satisfaction among physicians working in three university hospitals in Poland (1); to assess whether the physicians have the intention to migrate and what the main reasons for migration are (2); and to identify the actions that might be taken at the hospital level to mitigate physicians’ intentions to migrate (3). Methods: Cross-sectional study with both quantitative and qualitative components. In the quantitative part, an online questionnaire was distributed among physicians working in three university hospitals. A total number of 396 questionnaires were analyzed. In the qualitative part, in-depth interviews with six hospital managers were conducted and analyzed using thematic analysis. Results: On a scale from one “very dissatisfied” to six “very satisfied”, the mean career satisfaction of physicians was 4.0 (SD = 0.74). The item with the lowest mean concerned salary level (2.8, SD = 1.41). In the sample, 34% of physicians declared intentions to migrate from Poland. The main reasons for the intention to migrate were: Better working conditions abroad, higher earnings, the ability to maintain better work-life balance, better training opportunities abroad, and problems due to a stressful current workplace. Hospital managers considered the actions that can be taken at the hospital level to mitigate physicians’ migration to be specific to those focused on the working environment. Conclusions: Career development opportunities and features related to the working environment are the main factors influencing physicians’ satisfaction and migration intentions that can be modified at the university hospital level.